2015
DOI: 10.1038/cddis.2014.589
|View full text |Cite
|
Sign up to set email alerts
|

miR-34a regulates cell proliferation, morphology and function of newborn neurons resulting in improved behavioural outcomes

Abstract: miR-34a is involved in the regulation of the fate of different cell types. However, the mechanism by which it controls the differentiation programme of neural cells remains largely unknown. Here, we investigated the role of miR-34a in neurogenesis and maturation of developing neurons and identified Doublecortin as a new miR-34a target. We found that the overexpression of miR-34a in vitro significantly increases precursor proliferation and influences morphology and function of developing neurons. Indeed, miR-34… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
36
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 45 publications
(38 citation statements)
references
References 60 publications
2
36
0
Order By: Relevance
“…Furthermore, several other miRs have also been revealed to mediate the proliferation of neural cells. The overexpression of miR-125b, for example, inhibited the proliferation of neural stem/progenitor cells (22), and miR-34a was revealed to enhance cell proliferation and function of newly generated neurons, as well as improve behavioral outcomes (23). Furthermore, as patients with AD are characterized by learning and memory deficits (24), SAMP8 mice were used to investigate the effect of miR-135b on learning and memory behaviors in the present study.…”
Section: Discussionmentioning
confidence: 99%
“…Furthermore, several other miRs have also been revealed to mediate the proliferation of neural cells. The overexpression of miR-125b, for example, inhibited the proliferation of neural stem/progenitor cells (22), and miR-34a was revealed to enhance cell proliferation and function of newly generated neurons, as well as improve behavioral outcomes (23). Furthermore, as patients with AD are characterized by learning and memory deficits (24), SAMP8 mice were used to investigate the effect of miR-135b on learning and memory behaviors in the present study.…”
Section: Discussionmentioning
confidence: 99%
“…Chang and coworkers43 reported that the decreased expression of miR‐34a is crucial for the precise deployment of neural precursors to their correct destination. Similarly, Mollinari and coauthors44 identified DCX , a gene involved in neuronal migration disorders, as a new target of miR‐34a; they also observed stage‐specific effects of the overexpression of miR‐34a, detecting an increase in cell proliferation, and a delay in neuroblast migration. Thus, it could be hypothesized that the laminar disorganization and loss of radial orientation45 typically found in FCD type II may also be related to the dysregulation in the expression of hsa‐miR‐34a.…”
Section: Discussionmentioning
confidence: 85%
“…In human beings, there are ~1,600 miRNAs, which regulate more than half of protein coding genes, and each miRNA can regulate multiple proteins 174. Because the brain expresses several unique miRNAs such as miR-34a that control dendritic morphology, ion channel level, neuronal migration, and glial function microRNA may have an important implication for neuropsychiatric disorders 175. For example, miR-34a affected bipolar risk through directly impacting the ANK3 and CACNB3 expressions,176 and upregulation of miR-34a is associated with the risk of epilepsy 177.…”
Section: Epigenetics Of Epilepsymentioning
confidence: 99%
“…miRNAs regulates neural differentiation, maintenance, and plasticity. Fragile X mental retardation protein (FMRP) results in epilepsy associated with Fragile X syndrome by glutaminergic and GABAergic synaptic dysfunctions at the mRNA and protein levels 175177…”
Section: Epigenetics Of Epilepsymentioning
confidence: 99%